Single-step production of arabino-xylooligosaccharides by recombinant Bacillus subtilis 3610 cultivated in brewers' spent grain. (1st November 2018) - Amorim, Cláudia; Silvério, Sara C.; Silva, Soraia P.; Coelho, Elisabete; Coimbra, Manuel A.; Prather, Kristala L.J.; Rodrigues, Lígia R.
Graphical abstract: Highlights: B. subtilis 3610 wild type and mutants harboring the T. reesei xyn 2 gene produced AXOS. The mutant containing a secretion tag coupled to xyn 2 presented the highest yield. Optimal conditions were 20 g/L BSG, pH 7.0 and 45 °C at 12 h of fermentation. A mixture of AXOS with low amount of monosaccharides was produced. BSG one-step fermentation proved to be an effective approach for AXOS production. Abstract: Brewers' spent grain (BSG) is an inexpensive and abundant brewery by-product that can be used to produce prebiotic arabino-xylooligosaccharides (AXOS). In this study, Bacillus subtilis 3610 was used, for the first time, to produce AXOS through direct fermentation of BSG. Additionally, the microorganism was genetically modified to improve the AXOS production. The xylanase gene xyn2 from Trichoderma reesei coupled with a secretion tag endogenous to B. subtilis was cloned in pDR111 and integrated into its chromosome. After optimization by experimental design, AXOS with a degree of polymerization ranging from 2 to 6 were obtained. The maximum production yield expressed in xylose equivalents per amount of BSG (54.2 ± 1.1 mg/g) represents an increase of 33% comparing to the wild type. When compared with the enzymatic hydrolysis process, single-step fermentation with B. subtilis proved to be a very promising low-cost strategy for the simultaneous production of AXOS and valorization of BSG.